2017
DOI: 10.1097/pcc.0000000000001168
|View full text |Cite
|
Sign up to set email alerts
|

A Method to Account for Variation in Congenital Heart Surgery Length of Stay*

Abstract: We developed a statistically valid procedure-based categorical variable and multivariable model for length of stay of congenital heart surgeries. The Surgical Length Categories and important a priori and postoperative factors may be used to pursue a predictive tool for length of stay to inform scheduling and bed management practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Implementation of this approach is predicated on the ability to predict patient CICU LOS prior to surgical scheduling. We have previously demonstrated that pre-operative characteristics of this patient population can be used to predict post-operative CICU LOS with operationally adequate accuracy, and have incorporated these models into local capacity predictions (4,6). In short, we derived Congenital Heart Surgical Stay categories, which closely approximate STAT Categories, to identify those patients with a short anticipated CICU course of 1-2 days (category 1-2), compared to those with a longer anticipated LOS (categories 3-5) (4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Implementation of this approach is predicated on the ability to predict patient CICU LOS prior to surgical scheduling. We have previously demonstrated that pre-operative characteristics of this patient population can be used to predict post-operative CICU LOS with operationally adequate accuracy, and have incorporated these models into local capacity predictions (4,6). In short, we derived Congenital Heart Surgical Stay categories, which closely approximate STAT Categories, to identify those patients with a short anticipated CICU course of 1-2 days (category 1-2), compared to those with a longer anticipated LOS (categories 3-5) (4).…”
Section: Discussionmentioning
confidence: 99%
“…In total, there were 14,526 admissions. Descriptive data of the informing surgical population is included in recent reports of our program (4,6). In brief, these admissions are typically comprised of 19% neonates (<30 days); 32% infants (30 days to <1year), 41% children (1 to <18 years) and 9% over age 18 years, with surgical complexity according to The Society of Thoracic Surgeons-European Association for Cardio-Thoracic Surgery (STAT) Category 1 25%,Category 2 29%, Category 3 15%, Category 4 25% and Category 5 5%.…”
Section: Participantsmentioning
confidence: 99%
“…22,24,26,28,30,38,43,46,51,54,[56][57][58][59][60]62,63,[65][66][67]69,70,73,82 ** Patient drugs administered. 20,32,46,48,49,51,66,76,81,84 † † An event occurring during the hospital stay, for example, development of complications. 21,23,24,26,30,42,47,48,55,81 ‡ ‡ Patient risk scores, for example, Injury Severity Score.…”
Section: Data Sources and Input Variablesmentioning
confidence: 99%
“…20,32,46,48,49,51,66,76,81,84 † † An event occurring during the hospital stay, for example, development of complications. 21,23,24,26,30,42,47,48,55,81 ‡ ‡ Patient risk scores, for example, Injury Severity Score. 7,21,24-26,29,33,34,36-38,41,43, LOS modeling format was a continuous variable without transformation, a continuous variable with transformation (logarithmic or polynomial), or a discrete variable in 54.1% (40/74), 21.6% (16/74), and 24.3% (18/74) of the articles, respectively.…”
Section: Data Sources and Input Variablesmentioning
confidence: 99%
“…Many factors influence resource utilisation and Paediatric Cardiac ICU length of stay, including admitting diagnosis, surgical operation, post-operative complications, and unplanned hospital and Cardiac ICU readmissions. [1][2][3][4][5][6][7][8][9][10] Beyond severity of illness, variation in clinical outcomes is driven by individual providers' perceptions of "optimal care" and the system's ability to deliver the provider's construct to the patient. However, the downstream influence of provider perception on care delivery is not routinely assessed.…”
mentioning
confidence: 99%